The life of Marriage (Hekima Review, 2016)
I would like to live in heaven with angelsBut as I don’t have wings I don’t dare go to heavenThe heavens belong to me as my marriage is heaven on earth over this subsoilThe sweetness of my spouse is her virginity, a lighthouse without screens